Stereoselective Synthesis of the C(1)-C(19) Fragment of Tetrafibricin - Lira, Ricardo (2007)
[Image: see text] A stereoselective synthesis of the C(1)-C(19) fragment of tetrafibricin has been accomplished via a highly diastereoselective double allylboration reaction of 6, 7, and 8, and an iodonium-ion promoted urethane cyclization for the installation of the C(15) alkoxy function in 3.